Array Mutual Coupling Reduction Using L-Loading E-Shaped Electromagnetic Band Gap Structures - Tao Jiang; Tianqi Jiao; Yingsong Li (International Journal of Antennas and Propagation)
A mutual coupling reduction method between microstrip antenna array elements is proposed by using periodic L-loading E-shaped electromagnetic band gap structures. Two identical microstrip patch antennas at 2.55 GHz are settled together and used to analyze the performance of the designed two-element antenna array. The two antenna elements are settled with a distance of about 0.26λ. To reduce the mutual coupling, the L-loading E-shaped electromagnetic band gap structures are used between these antenna elements. The simulated and measured results show that the isolation of the antenna array reaches 38 dB, which has a mutual coupling reduction of 26 dB in comparison with the antenna array without the decoupling structures.